Are Polyunsaturated Fatty Acids Implicated in Histaminergic Dysregulation in Bipolar Disorder?: AN HYPOTHESIS - Riveros, María E.; Retamal, Mauricio A. (Frontiers in Physiology, 2018)
Bipolar disorder (BD) is an extremely disabling psychiatric disease, characterized by alternate states of mania (or hypomania) and depression with euthymic states in between. Currently patients receive pharmacological treatment with mood stabilizers, antipsychotics, and antidepressants. Unfortunately, not all patients respond well to this type of treatment. Bipolar patients are also more prone to heart and metabolic diseases as well as a higher risk of suicide compared to the healthy population. It has been reported a reduction in n-3 essential fatty acids in specific brain regions in BD patients. Accordingly, a diet rich in n-3 has beneficial effects in patients, while their absence or high levels of saturated fatty acid in the diet, is related to the risk of developing the disease. These observations could be related to findings showing that diet supplementation with polyunsaturated fatty acids ( e.g., Omega-3) can increase Na+/K+ ATPase activity in rat neurons. On the other hand, the histamine system is likely to be involved in the pathophysiology of several psychiatric diseases such as bipolar depression and alcoholism, diseases that are frequently comorbid and share genetic risk factors. Histamine is a neuromodulator involved in arousal; motivation and energy balance, drugs acting on the H3 receptor have shown potential as antidepressants and antipsychotics. The Histaminergic system as other neurotransmission systems can be altered by fatty acid membrane composition. The purpose of this review is to explore how polyunsaturated fatty acids content alterations are related to the histaminergic system modulation and their impact in BD pathophysiology.